Stylet Probing Behavior of Two Bactericera (Hemiptera: Psylloidea: Triozidae) Species on Host and Nonhost Plants. Issue 4 (12th April 2021) - Mustafa, Tariq; Horton, David R; Cooper, W Rodney; Zack, Richard S; Thinakaran, Jenita; Karasev, Alexander V; Munyaneza, Joseph E
Abstract: Understanding host use by psyllids (Hemiptera: Psylloidea) benefits from comparative studies of behavior on host and nonhost plant species. While most psyllid species develop on one or a few closely related plant species, some species are generalized enough to develop on species across plant families. We used electropenetography (EPG) technology to compare probing activities of an oligophagous psyllid ( Bactericera cockerelli (Šulc)) and a host-specialized psyllid ( Bactericera maculipennis ) on two species of Solanaceae (potato, Solanum tuberosum L. and matrimony vine, Lycium barbarum L.) and two species of Convolvulaceae (field bindweed, Convolvulus arvensis L. and sweet potato, Ipomoea batatas ). Bactericera cockerelli develops on all four species, albeit with longer development times on Convolvulaceae. Bactericera maculipennis develops only on Convolvulaceae. Bactericera cockerelli fed readily from phloem of all four species, but the likelihood of entering phloem and duration of time in phloem was reduced on suboptimal hosts (Convolvulaceae) relative to behavior on Solanaceae. We observed instances of cycling between bouts of phloem salivation and ingestion in assays of optimal (Solanaceae) hosts not observed on Convolvulaceae. The Convolvulaceae-specialized B. maculipennis (Crawford) failed to feed from phloem of nonhosts (Solanaceae). Both psyllid species readily ingested from xylem of all plant species, irrespective of host status. Our finding that phloem feeding by B. maculipennis did not occur on potato has implications for understanding epidemiology of phloem-limited psyllid-vectored plant pathogens. Our results also showed that EPG assays detect subtle variation in probing activities that assist in understanding host use by psyllids.